2000
DOI: 10.3168/jds.s0022-0302(00)75164-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation of Susceptibility to Mycobacterium avium subsp. paratuberculosis Infection in Dairy Cattle

Abstract: Paratuberculosis is an infectious disease that is not easily amenable to classical control methods such as treatment and vaccination. Experimental animal models suggest that there could be genetic factors responsible for susceptibility or resistance to infection with the causative agent, Mycobacterium avium subsp. paratuberculosis. The aim of this study was to estimate genetic variation in susceptibility to paratuberculosis in Dutch dairy cattle. Data collected during a vaccination trial, conducted from 1984 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
1
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(107 citation statements)
references
References 16 publications
9
94
1
3
Order By: Relevance
“…Variable breed or strain resistance to mycobacterial infection has been well described in mice (see Section 7.1, murine models). Genetic resistance has also been described in cattle (Koets et al, 2000;Mortensen et al, 2004) and red deer (Mackintosh et al, 2000), but not in goats and sheep. Breed or strain of animal should be specified in the event that an associated resistance might exist.…”
Section: Breed/strain Of Animalmentioning
confidence: 98%
“…Variable breed or strain resistance to mycobacterial infection has been well described in mice (see Section 7.1, murine models). Genetic resistance has also been described in cattle (Koets et al, 2000;Mortensen et al, 2004) and red deer (Mackintosh et al, 2000), but not in goats and sheep. Breed or strain of animal should be specified in the event that an associated resistance might exist.…”
Section: Breed/strain Of Animalmentioning
confidence: 98%
“…While in mice and humans several genes involved in resistance to mycobacterial infections have been studied in detail, the data regarding cattle are scarce. Koets et al (2000) indicated the presence of genetic variation in the susceptibility to paratuberculosis. Recent studies point to various chromosome regions or quantitative trait loci (QTL) associated with paratuberculosis (Gonda et al, 2006(Gonda et al, , 2007.…”
Section: Introductionmentioning
confidence: 99%
“…If the disease is not efficiently controlled it is guaranteed to spread MAP to most animals in the herd, although the genetic influences in the susceptibility of cattle to paratuberculosis have been reported (Koets et al, 2000). Subsequently, as a result of different stress factors e.g.…”
mentioning
confidence: 99%